Analisis Kinerja Keuangan Pemerintah Provinsi Kalimantan Timur Sebelum dan Selama Pandemi Covid-19 - Yusrina Hayfani; Sintia Sintia; Rismansyah Jatmiko (Jurnal Publikasi Ilmu Manajemen, 2023)
The Covid-19 pandemic that swept across the globe had a significant impact on Indonesia's economy. The purpose of this study is to compare the East Kalimantan Provincial Government's financial performance prior to and during the Covid-19 pandemic. The East Kalimantan Provincial Government's audited financial statements for the 2019 and 2020 fiscal years served as the secondary data for this descriptive quantitative study. Literature review was used as the data collection in this study. The East Kalimantan Provincial Government's overall financial performance in dealing with the Covid-19 pandemic is shown by the analysis of local government financial performance using financial ratios. The East Kalimantan Provincial Government has been able to maintain financial stability and maximize local revenue despite several financial aspects that have decreased and need to be improved, such as the efficiency of financial management, a more balanced allocation of expenditures between operational and capital, and regional growth that has decreased as a result of Covid-19.